Analysis of China's olefin industry with a system optimization model – With different scenarios of dynamic oil and coal prices. (December 2019) - Xu, Zhongming; Zhang, Yaru; Fang, Chenhao; Yu, Yadong; Ma, Tieju
Abstract: Recently, China produces olefins increasingly from coal, although OTO (oil-to-olefins) is still dominating China's olefin industry. With the uncertain future dynamics of oil and coal prices, as well as environmental issues, how should China configure its future olefin industry? And what kind of carbon emission controlling policies should be implemented if more olefins would be produced with CTO (coal-to-olefins) in China? This paper develops a system optimization model to explore these questions. With four different scenarios of oil and coal prices, we first explore the optimal configuration of China's olefin industry without considering controlling carbon emission; then we explore the situation in which new CTO capacity must implement CCS (carbon capture and storage) for controlling carbon emission. The results of our study imply that investing in CTO technology in China is not a wrong direction, especially as a technology stock for energy safety, and it could be a good regulation to require CTO to implement CCS for achieving both economic and environmental values. Highlights: This study first develops an optimization model of China's olefin industry. Then explores the optimal configurations under four scenarios of oil and coal prices. And also analyzes the impact of implementing CCS to CTO. The study implies that investing in CTO technology in China is not a wrong direction. And also implies it could be a good regulation to require CTO to implement CCS.